Major suppliers of hand-knotted carpets: Iran, Afghanistan, Turkey, Romania with summary of recent developments in the world market - International Trade Center UNCTAD/GATT. (Geneva : International Trade Center UNCTAD/GATT, 1983)
This volume gives a summary of recent developments in world market and country chapters on Iran, Afghanistan, Turkey and Romania, with data and comments on production, exports, product characteristics, export marketing and addresses of selected producers
VolumeIII
osc 23/07/2019
Loans
Keywords: Rug and carpet industry